ELASTISITAS PERMINTAAN JASA TRANSPORTASI KERETA API DI KOTA MALANG - Tofan Lore Firmansyah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
Method which is used in this research technique analyse elasticity, technique analyse this represent technique with aim to to know how big mount elasticity request of train transportation service in Malang City. From result of examination obtained conclusion of cause the happening of Perfect Elasticity at Economic Class, because of low price storey of society tend to to chosen cheap price as according to its production level. So that in middle economic level downwards more opting society of Economic class train than Business class train and also Executive. Executive class pertained elastic in of perfection because of how price will buy. Because of the class have different level. In this class met many middle-weight consumer to to the. While Business class train is including level . Ing strata third class at Business class train reside in between Economic class and Executive class. So that at this class of diffraction enjoyed